1970
DOI: 10.1104/pp.45.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Studies on the Proteins of the Peanut Cotyledon and Embryonic Axis

Abstract: Subcellular fractions fronm the cotyledon obtained bv differential aind density gradient centrifugation, and extracts of total proteins from botlh cotyledon and axial tissues were analyzed by diethvlaminoethyl cellulose clironiatography, zone electrophoresis, ultracentrifugatioti, immunodiffusion, and immunoelectrophoresis. Fractionation and characterization of proteinis in subcellular organelles of the peanut reaffirin that a-arachin is located in the protein bodies of the cells. Results obtained bv diethlv-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1971
1971
1988
1988

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The two bands corresponding to a-arachin have slightly different mobilities but show a continuous precipitin arc. These two zones were separated by starch gel electrophoresis and were shown to be antigenically identical by double diffusion (Neucere, 1971). a2-Conarachin remains at the interface of the stacking gel and the running gel.…”
Section: Resultsmentioning
confidence: 99%
“…The two bands corresponding to a-arachin have slightly different mobilities but show a continuous precipitin arc. These two zones were separated by starch gel electrophoresis and were shown to be antigenically identical by double diffusion (Neucere, 1971). a2-Conarachin remains at the interface of the stacking gel and the running gel.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in proteins between different parts of a seed have been documented for soybean (Alekseeva and Kovarskaya, 1978;Knypl and Radziwonowska, 1979;Meinke, Chen, and Beachy, 1981), castor bean (Sobolev and Dmitrieva, 1983;Kermode et al, 1985), mung bean (Manikam and Carlier, 1980), and peanut (Neucere and Ory, 1970). In soybean, the buffer extractable proteins of the cotyledons, unlike those ofthe embryo axis, contain the 11S acidic and basic glycinin components, whereas a 24 kD protein of unknown function is specific to the axis (Meinke et al, 1981).…”
Section: -mentioning
confidence: 99%
“…In castor bean, certain glycoproteins and lectins, RCA 1 and ricin, occur only in the endosperm. Neucere and Ory (1970) believe that proteins of the embryonic axis are immunologically different from those of the cotyledons in peanut.…”
Section: -mentioning
confidence: 99%
“…There have been many investigations on the reserve proteins of peanuts because of their potential usefulness as food supplements. In general, these studies have shown that most of the proteins are easily extractable (Altschul et al, 1961(Altschul et al, , 1964aDawson, 1971; Dechary and Altschul, 1966;Dechary et al, 1961) and can be separated into two major fractions, arachin and conarachin (Daussant et al, 1969a,b;Dechary et al, 1961; Evans et al, 1962;Neucere, 1969; Neucere and Ory, 1970). More extensive purification of these two fractions (Dawson, 1971;Evans et al, 1962;Tombs, 1965;Tombs and Lowe, 1967;Neucere, 1969) has revealed that they are composed of complex large molecular weight globulins (a-arachin, a-conarachin), plus some other closely related components, not completely separated by the usual techniques.…”
mentioning
confidence: 99%